BACKPROPAGATION ANALYSIS IN SELECTING THE BEST ARCHITECTURE TO PREDICTION THE NUMBER OF POPULATION OF SIANTAR MARTOBA - Afatandio, Arril; Purba, Yuegilion Pranayama; Safii, Muhammad (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Basically, this region experiences growth every year. The negative impact of uncontrolled population growth will cause social inequality and poverty and affect the progress and prosperity of the region. Judging from the number of residents registered with the Population and Civil Registration Service, Siantar Martoba District has a fairly high population growth rate, so it is necessary to predict the future population. In making a prediction, a good method is needed to solve a problem. In this research, a backpropagation algorithm was used using five architectures, namely architecture 4-71-1, 4-31-1, 4-16-1, 4-72-1, 4-83-1. From the results of tests carried out using data on the population of Siantar Martoba, the best architecture was obtained, namely architecture 4-31-1 with a mean squared error for training of 0.00009960 and a mean squared error for testing of 0.000099957 and obtained an epoch of 14012 iterations with a time of 01 minutes 40 seconds. It was concluded that this method can predict the population of Siantar Martoba in the future using Matlab R2011a, thus obtaining a population of Siantar Martoba of 36470 people.            Keywords: architecture; backpropagation; pematangsiantar; population; welfare  Abstrak: Pada dasarnya, wilayah ini mengalami pertumbuhan setiap tahunnya. Dampak negatif pertumbuhan penduduk yang tidak terkendali akan menyebabkan kesenjangan sosial dan kemiskinan dan mempengaruhi kemajuan, kesejahteraan daerah tersebut. Dilihat dari jumlah penduduk yang terdaftar pada Dinas Kependudukan dan Pencatatan Sipil Kecamatan siantar martoba mempunyai laju pertumbuhan penduduk yang cukup tinggi, sehingga perlu dilakukan prediksi jumlah penduduk masa depan. Dalam melakukan sebuah prediksi dibutuhkan sebuah metode yang baik dalam menyelesaikan sebuah permasalahan, dalam penelitian ini digunakan algoritma backpropagation dengan menggunakan lima arsitektur yaitu arsitektur 4-71-1, 4-31-1, 4-16-1, 4-72-1, 4-83-1. Dari hasil pengujian yang telah dilakukan dengan menggunakan data jumlah penduduk siantar martoba diperoleh arsitektur terbaik yaitu arsitektur 4-31-1 dengan nilai mean squared error pelatihan 0.00009960 dan mean squared error pengujian 0.000099957 dan memperoleh epoch 14012 iterations dengan waktu 01 menit 40 detik. Disimpulkan bahwa metode ini dapat memprediksi jumlah penduduk Siantar Martoba di masa depan dengan menggunakan Matlab R2011a, sehingga memperoleh jumlah penduduk siantar martoba sebanyak 36470 Jiwa. Kata kunci: arsitektur; backpropagation; pematangsiantar; kependudukan; kesejahteraan